1999
DOI: 10.1046/j.1365-2958.1999.0erat.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the A‐band polysaccharide sugar D‐rhamnose requires Rmd and WbpW: identification of multiple AlgA homologues, WbpW and ORF488, in Pseudomonas aeruginosa

Abstract: (1994) Identification of amino acid residues involved in the activity of phosphomannose isomerase-guanosine 5Ј-diphospho-D-mannose pyrophosphorylase, a bifunctional enzyme in the alginate biosynthetic pathway of Pseudomonas aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(73 citation statements)
references
References 61 publications
4
69
0
Order By: Relevance
“…In P. aeruginosa, there can be an overlap between EPS synthesis gene functions and LPS functions (23). Thus, pslA could be involved in LPS synthesis and an LPS modification could be responsible for the abnormal biofilm phenotype of pslA mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In P. aeruginosa, there can be an overlap between EPS synthesis gene functions and LPS functions (23). Thus, pslA could be involved in LPS synthesis and an LPS modification could be responsible for the abnormal biofilm phenotype of pslA mutants.…”
Section: Resultsmentioning
confidence: 99%
“…We know that motility is involved in biofilm formation, but both the twitching and swimming motilities of a pslA mutant were comparable to those of the parent (Table 2). There is evidence that LPS influences biofilm architecture (23). One might imagine that the psl gene cluster affects LPS synthesis, but at least by comparing LPSs in silver-stained sodium dodecyl sulfatepolyacrylamide gels, the mutant and the parent were indistinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…1; Table 2), psl may regulate or constitute a portion of the LPS synthesis pathway. LPS has been implicated in the architecture of P. aeruginosa biofilms (44), and a prior study suggested that pslB (designated ORF 488) may be involved in A-band LPS synthesis (45). To determine if the psl-dependent effects on biofilm formation are LPS related, we compared the LPS profiles of PAO1, WFPA60, a PAO1 algC mutant, and the corresponding algC complemented strain.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…In addition to LPS biosynthesis, rml and xanB orthologues in Pseudomonas aeruginosa, Escherichia coli, and X. campestris pv. campestris are required for the biosynthesis of exopolysaccharides (19,32). The xanB, rmlA, and rmlC mutants all produced lower amounts of EPS when assayed by the phenol-sulfuric acid method for total carbohydrates (13) (not shown), suggesting that the three genes are also involved in EPS biosynthesis in S. maltophilia WR-C.…”
mentioning
confidence: 99%